Evaluation of storm runoff pathways in steep nested catchments draining a Japanese cypress forest in central Japan: a geochemical approach - Gomi, Takashi; Asano, Yuko; Uchida, Taro; Onda, Yuichi; Sidle, Roy C; Miyata, Shusuke; Kosugi, Ken'ichiro; Mizugaki, Shigeru; Fukuyama, Taijiro; Fukushima, Takehiko (Hydrological processes, 2010)
Flow pathways were examined using both hydrometric observations and geochemical tracers in a 4·9 ha nested Japanese cypress watershed. Hydrometric observations on hillslopes showed measurably significant amounts of overland flow for all types of hillslopes, regardless of the condition of the understorey vegetation. The relationships between small and large plots suggested that all overland flows generated on hillslopes were not transferred to the channels. Storm water chemistry was sampled for storm events with total precipitation >80 mm. On the basis of the final mixing analysis, K⁺ was used to separate overland flow from other components. The sizes of storm events did not affect the patterns of the flow components separated by δ¹⁸O (new water) and K⁺ (reacted water). On the basis of the hydrograph separation by δ¹⁸O, small catchments tended to have smaller old water components regardless of vegetation type, which agreed with the ephemeral nature of flow conditions in these small catchments. Hence, old and new water ratios between small and large catchments were found to vary greatly among storm events. Overland flow contributed up to 30% of storm runoff in specific small catchments with sparse understorey vegetation, whereas overland flow contribution attributed to 1-2% in catchments with fern and shrub vegetation cover. The contributions of overland flow on catchment runoff decreased with increases in the drainage area. The combination of both hydrometric observations and geochemical tracers can facilitate the understanding of the links between hillslopes and streams related to overland flow and material dynamics. Copyright © 2010 John Wiley & Sons, Ltd.